The so-called insula dei Lottatori and block V, III in Ostia: the combination of terrestrial laser scanner (TLS) and drones (UAS) in the field of cultural heritage - Marco Cavalieri; Anthony Peeters (Groma, 2024)
The paper illustrates the 3D survey of the so-called Caseggiato dei Lottatori and the Block V, III in Ostia, where the combination of terrestrial laser scanning survey with UAS photogrammetry was employed. The result is a high-quality 3D model and a set of high-resolution images, essential tools for further research, and for its proper conservation. This article describes in detail the general workflow followed, from survey planning to data archiving. This last stage, still too often disregarded, is placed in its theoretical context by highlighting the main standards available today.